No life, no land: Homicide and dispossession in Mexico - Meneses-Reyes, Rodrigo; García-Tejeda, Enrique; Fondevila, Gustavo; Massa, Ricardo (My University, 2021)
Literature suggests that the spatial concentration of violence can contribute to destabilizing property relations. In this context, there is an underexplored area related to the study of the relationship between specific forms of violence (homicide) and dispossession – defined as the criminal intent of taking property through violence and force. This study seeks to fill this gap by testing the violence/property hypothesis using information from 2471 sub-national units of Mexico for the period 2015–2019. Findings confirm a spatial association between dispossession and homicide that is not randomly distributed across space. Moreover, it is found to be neither fixed nor dichotomous. This could open a debate on the causal direction between homicidal violence and property dispute.